Oral health knowledge, behavior, and barriers to dental care of adult Jordanians adorning oral and/or perioral piercings-a cross-section study - Alshatrat, Sabha Mahmoud; Ramadan, AbdelRahman Murtada; Hammouri, Hanan M.; Khader, Yousef Saleh; Al-Bakri, Isra Abdulkarim; Falah, Tamadur Mahmoud; Tabnjh, Abedelmalek Kalefh (Frontiers in Oral Health, 2025)
BackgroundThe global prevalence of oral piercings is increasing, and there are mounting concerns about complications associated with oral and/or perioral piercings. Providing precautionary advice about piercing complications is important.Aimsto determine the oral health knowledge, behavior, and barriers to dental care for oral and/or perioral piercings in adult Jordanians.MethodsA web-based, anonymous, self-administered closed-end questionnaire was distributed across Jordan. It included questions regarding oral health knowledge, behavior, and barriers to dental care.ResultsAbout (81.5%) liked how it looked. Most participants (49%) reported no complications, while 35% reported pain. The beauty parlors placed 76% of piercings and were also the source of help in case of complications. Most common barriers to seeking regular care were the perception that health professionals would refuse to treat them and the lack of confidence in the health professionals (90%) to treat the complications. Most participants (47%) brushed their teeth at least twice a day, and 68% spent 1–2 min brushing. Most participants (86%) knew that sugars and sweets caused dental caries. Also, (73%) believed bleeding gums was abnormal.ConclusionThis study suggests that adult Jordanians primarily choose piercings for aesthetic reason, with beauty parlors being the preferred place for both piercings and assistance in the event of complications. The lack of trust in healthcare professionals, with the believe that experts may refuse treatment were the reasons for participants avoided seeking regular dental care, which might increase risk of periodontal and gingival diseases.